Supervision and Performance of Early Childhood Teachers: An Analysis Across Kindergarten Accreditation Levels - Shafira, Nanda Afriyani; Rahman, Taopik; Sianturi, Risbon (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2025)
This study aims to examine the effect of supervision on the performance of kindergarten teachers in Baleendah District, Bandung Regency, by taking into account the schools’ accreditation levels. The research is motivated by the issue of kindergarten teachers’ performance, which is considered suboptimal, thus requiring managerial strategies such as supervision to improve teachers’ work quality. This study employed a quantitative approach, with data collected through questionnaires and interviews with principals and teachers. The results indicate that supervision has a positive and significant effect on kindergarten teachers’ performance. Moreover, there are slight variations in the influence of supervision depending on the accreditation level. These findings highlight the crucial role of principals in conducting effective and sustainable supervision, particularly in the context of early childhood education management. It is expected that the results can serve as a reference for school principals and education managers in designing more structured and sustainable supervision programs to directly enhance the quality of kindergarten teachers’ performance.